2001
DOI: 10.1080/027868201300082148
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Ambient Fine Particles into the Indoor Environment

Abstract: Several recent studies have indicated signi cant health risks associated with exposure to ne particles as measured outdoors. However, much of the exposure is believed to have occurred indoors. Consequently, there is considerable interest in the relationship between indoor and outdoor ne particles. This paper describes some results from a study in which the processes of particle removal from in ltrating air by building envelopes are simulated in a chamber. The chamber consists of two compartments, each having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 6 publications
6
87
0
3
Order By: Relevance
“…For ultrafine particulate matter, indoor concentrations were generally lower than outdoor levels if indoor sources were not present, but cooking activities led to substantial increases in concentrations. The lower indoor -outdoor ratios for ultrafine particles, when compared with PM 2.5 , are supported by past studies ( Long et al, 2001 ) and can be related to greater depositional losses from diffusion and lower penetration rates (Mosley et al, 2001 ). Specific cooking activities have been implicated in elevated ultrafine concentrations in residential settings (e.g., Abt et al, 2000b;Wallace, 2000 ), the effect of which is magnified in a food court with numerous grills.…”
Section: Discussionmentioning
confidence: 57%
“…For ultrafine particulate matter, indoor concentrations were generally lower than outdoor levels if indoor sources were not present, but cooking activities led to substantial increases in concentrations. The lower indoor -outdoor ratios for ultrafine particles, when compared with PM 2.5 , are supported by past studies ( Long et al, 2001 ) and can be related to greater depositional losses from diffusion and lower penetration rates (Mosley et al, 2001 ). Specific cooking activities have been implicated in elevated ultrafine concentrations in residential settings (e.g., Abt et al, 2000b;Wallace, 2000 ), the effect of which is magnified in a food court with numerous grills.…”
Section: Discussionmentioning
confidence: 57%
“…In recent studies (Liu and Nazaroff 2001, Mosley et al 2001, Vette et al 2001, penetration factors of particles within range of 0.5-2.5 µm have been between 0.5 and 1 depending on the dimensions of studied cracks. These results cover the size distribution of fungal spores; and the peak of spores of 1-2 µm seems to be very capable for penetration if the crack height is higher than 0.1 mm (Liu and Nazaroff 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Vette et al (2001) report penetration factors 0.5-0.8 for particles in a size range of 0.5-2.5 µm. Mosley et al (2001) have found that at a pressure of 5 Pa 40% of 2 µm particles and <1% of 5 µm particles penetrate through horizontal slits of height 0.508 mm. In a study (Liu and Nazaroff 2001) particles of 0.1-1.0 µm are predicted to have the highest penetration efficiency, nearly unity for crack heights of 0.25 mm or larger at pressure difference of ≥4 Pa.…”
Section: Crawl Space Base Floor Outdoor Air Flow Outdoor Air Flowmentioning
confidence: 99%
“…Previous studies have demonstrated correlations between F inf and a number of building, meteorological and behavioral factors; however, such studies do not use data readily available for large populations. Factors found to be related to F inf include housing variables such as age, size, value, square footage, and ventilation conditions (Wallace, 1996;Sherman and Dickerhoff, 1998;Ozkaynak et al, 1999;Ebelt et al, 2000;Sherman and Matson, 2001;Thornburg et al, 2001;McKone et al, 2002;Hanninen et al, 2005;Chan et al, 2005); meteorological factors including temperature and exposure to wind and precipitation (Sherman and Dickerhoff, 1998;Chao and Tung, 2001;McKone et al, 2002); and occupant behaviors and characteristics, such as occupant income, window opening, and use of air conditioners and air filters (Sherman and Dickerhoff, 1998;Mosley et al, 2001;Janssen et al, 2002;Wallace et al, 2003;Koenig et al, 2005). A study by Chan et al (2005) analyzed approximately 70,000 air leakage measurements (a parameter related to F inf ) in the United State to determine predictive housing characteristics and found year of construction, size of dwelling and whether the dwelling was either energy-efficient or occupied by a low-income family to be important predictors of normalized leakage.…”
Section: Introductionmentioning
confidence: 99%